Persistent Plasmodium falciparum Infection in Women With an Intent to Become Pregnant as a Risk Factor for Pregnancy-associated Malaria. (4th May 2018) - Tuikue Ndam, Nicaise; Tornyigah, Bernard; Dossou, Akpéyédjé Yannelle; Escriou, Guillaume; Nielsen, Morten A; Salanti, Ali; Issifou, Saadou; Massougbodji, Achille; Chippaux, Jean-Philippe; Deloron, Philippe
Abstract : A preconceptional cohort of 275 nulligravidae was established in Benin, and 68 confirmed pregnancies were followed up until delivery. Women infected with Plasmodium falciparum before pregnancy were more likely to be infected during pregnancy. Most infections during pregnancy were acquired before pregnancy. Abstract: Background: Pregnant women are more susceptible to Plasmodium falciparum than before pregnancy, and infection has consequences for both mother and offspring. The World Health Organization recommends that pregnant woman in areas of transmission receive intermittent preventive treatment (IPTp) starting in the second trimester. Consequently, women are not protected during the first trimester, although P. falciparum infections are both frequent and harmful. Methods: A cohort of nulligravid women was followed up during subsequent pregnancy. Malaria was diagnosed by means of microscopy and polymerase chain reaction. Parasites were genotyped at polymorphic loci. Results: Among 275 nulligravidae enrolled, 68 women became pregnant and were followed up during pregnancy. Before pregnancy, P. falciparum prevalence rates were 15% by microscopy and 66% by polymerase chain reaction. Microscopic infection rates increased to 29% until IPTp administration, and their density increased by 20-fold. Conversely, submicroscopic infection rates decreased. After IPTp administration, all types of infections decreased, but they increased again late in pregnancy. The risk of infection during pregnancy was higher in women with a microscopic (odds ratio, 6.5; P = .047) or submicroscopic (3.06; P = .05) infection before pregnancy and was not related to the season of occurrence. Most infections during pregnancy were persistent infections acquired before pregnancy. Conclusions: Microscopic and submicroscopic malaria infections were frequent in nulligravid women from south Benin. During the first trimester of pregnancy, microscopic infections were more frequent, with a higher parasite density, and mainly derived from parasites infecting the woman before conception. Preventive strategies targeting nonpregnant women with a desire for conception need to be designed.